2010
DOI: 10.1093/toxsci/kfq288
|View full text |Cite
|
Sign up to set email alerts
|

Clearance Kinetics of Fullerene C60 Nanoparticles from Rat Lungs after Intratracheal C60 Instillation and Inhalation C60 Exposure

Abstract: Fullerene (carbon sixty [C(60)]) has potential industrial and medical applications. In the future, people working in or residing near manufacturing facilities may be exposed to C(60). Therefore, quantitative data on long-term C(60) clearance from the lungs are required. To estimate the clearance rate and deposition fraction of C(60) from inhalation exposure, the C(60) burden in the lungs, liver, and brain of rats was determined after intratracheal instillation and inhalation. Male Wistar rats were intratrachea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 27 publications
4
62
0
3
Order By: Relevance
“…Also, it is difficult to compare the quantity of nanoparticles used in our simulations with real-world nanoparticle exposure data: for airborne pollutants, exposure is usually reported as mass of pollutant per volume of air for a given exposure time, which is difficult to correlate with the actual quantity of pollutant deposited on lung membranes. In some experiments, nanoparticle suspensions were instilled intratracheally into mice [37,38] or rats [39]. In those cases, assuming that all nanoparticles deposit on lung membranes and knowing approximately the surface area of mice lungs [40], one can estimate the exposure in terms of mass of the nanoparticles per unit of lung membrane surface, or in terms of total nanoparticle surface over lung membrane surface.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is difficult to compare the quantity of nanoparticles used in our simulations with real-world nanoparticle exposure data: for airborne pollutants, exposure is usually reported as mass of pollutant per volume of air for a given exposure time, which is difficult to correlate with the actual quantity of pollutant deposited on lung membranes. In some experiments, nanoparticle suspensions were instilled intratracheally into mice [37,38] or rats [39]. In those cases, assuming that all nanoparticles deposit on lung membranes and knowing approximately the surface area of mice lungs [40], one can estimate the exposure in terms of mass of the nanoparticles per unit of lung membrane surface, or in terms of total nanoparticle surface over lung membrane surface.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary C 60 burden decreased with time and depended on the C 60 concentration administered, while the concentration of C 60 in the liver and brain was below 8.9 ng/g tissue, the detection limit of the method employed. 25 A comprehensive review on fullerene toxicity is given by Kolosnjaj et al 26 These authors review the works on fullerene toxicity and conclude that very little evidence gathered since the discovery of fullerenes indicates that C 60 is toxic. Furthermore, it has been demonstrated that unmodified C 60 fullerenes are not toxic to cells and therefore could be useful for several biological applications.…”
Section: ' Discussionmentioning
confidence: 99%
“…After inhalation exposure, 25% and 35% cleared at 168 and 336 days post‐exposure compared with the burden at 1 day post‐exposure in rats (Mercer et al ., 2013). In contrast, spherical C 60 nanoparticles were cleared from the lungs much faster than MWCNTs [half‐life < 1 month (Shinohara et al ., 2010)] although C 60 and CNTs are both carbon allotropes, and both have a graphene structure. For other poorly soluble fibers, the pulmonary clearance was similarly slow to that observed in the present study [crocidlite and amosite, half‐life > 13 months (Hesterberg and Hart, 2000); silicon carbide whisker, half‐life 16 months (Akiyama et al ., 2007)].…”
Section: Discussionmentioning
confidence: 99%